The Mueller Report The Final Report of the Special Counsel on Russian Interference in the 2016 Presidential Election - Mueller, Robert S. (Dover Publications, 2019)
The full report, as released on April 18, 2019, by the U.S. Department of Justice, without analysis or commentary and with nothing subtracted except for redactions by the Department of Justice